SAT0349 Evaluation of standard swallowing function in assessing aspiration risk for patients with systemic sclerosis. (15th June 2017) - Yan, L; Yunfeng, P; Mengru, Y
Abstract : Background: Swallowing dysfunction is a common symptom of systemic sclerosis, which usually induce aspiration pneumonia to aggravate lung progress. It is necessary to screen swallowing disorders effectively at an early stage. Objectives: To investigate the value of standard swallowing function assessment (SSA) in aspiration screening for inpatients with Systemic sclerosis. Methods: SSA and Video fluoroscopic swallowing study (VFSS) were performed in 120 inpatients with Systemic sclerosis from March 2014 to September 2016.The sensitivity, specificity, positive predictive value and negative predictive value of SSA in the diagnosis of aspiration in patients were calculated by taking VFSS examination as the gold standard. The incidence of pneumonia in SSA-positive and SSA-negative patients were compared. Results: The diagnostic sensitivity of SSA was 81.2%, the specificity was 75%, the positive predictive value was 68.6% and the negative predictive value was 90.3%. The incidence of pneumonia in SSA positive patients was higher than that in SSA negative patients (54.1% vs 28.3%) (P<0.01). Conclusions: SSA is a valuable screening tool for the evaluation of aspiration risk in patients with Systemic sclerosis. References: Systemic Sclerosis with Multiple Pulmonary Manifestations. Kotnur MR, Suresh P, Reddy VS, Sharma T, Salim NA. J Clin Diagn Res. 2016 Jun;10(6):OD16–7. doi: 10.7860/JCDR/2016/18781.8032. Progression of esophageal dysmotility in systemic sclerosis. Vischio J, Saeed F, Karimeddini M, Mubashir A, Feinn R, Caldito G, Striegel K, Rothfield N. J Rheumatol. 2012 May;39(5):986–91. doi: 10.3899/jrheum.110923. Disclosure of Interest: None declared